2003
DOI: 10.1067/mva.2003.91
|View full text |Cite
|
Sign up to set email alerts
|

Advanced management of venous malformation with ethanol sclerotherapy: Mid-term results

Abstract: Absolute ethanol sclerotherapy can deliver excellent results as an independent therapy to the infiltrating type of extratruncular form of VM, which was once taboo because of prohibitively high morbidity. Absolute ethanol may be accepted as an effective treatment method because no recurrence has been observed in the relatively long-term observation period and the morbidity has been acceptable. However, it should be reserved only for individuals and centers with expertise. The morbidity involved should be clearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
186
0
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(205 citation statements)
references
References 9 publications
6
186
0
10
Order By: Relevance
“…This could indicate superior results with ethanol and numerous other studies have published similar findings (50,56,(73)(74)(75)(76)(77)(78).…”
Section: Treatment Effectivenesssupporting
confidence: 72%
“…This could indicate superior results with ethanol and numerous other studies have published similar findings (50,56,(73)(74)(75)(76)(77)(78).…”
Section: Treatment Effectivenesssupporting
confidence: 72%
“…Local wound care, compression dressings, special orthopaedic footwear and lifestyle modification may also be required to manage activities of daily living and improve the function of the limb. 14 A number of minimal invasive procedures are adopted for management of venous abnormalities. It includes pulse-dye laser therapy for port wine stain.…”
Section: J Dermatol Case Rep 2009 4 Pp 56-59mentioning
confidence: 99%
“…22 According to Lee BB et al, success rates using absolute alcohol have been reported in up to 95% with no evidence of recurrence. 23,24 Results In comparison to hemangiomas, vascular malformations diagnosed at birth shows no signs of involution with age and might expand close to puberty. In our case swelling was seen later in life, which was bluish in color and no signs of palpation or rise in temperature, leads to the diagnosis of venous malformation.…”
Section: Treatmentmentioning
confidence: 99%